Phytochemical Studies On Hylocereus Polyrhizus (Fruit And Stem) And Hylocereus Undatus (Fruit) - Foong, Shin Yee (2014)
The volatile constituents for the fruits of Hylocereus polyrhizus and Hylocereus undatus were isolated by vacuum distillation and analysed by capillary GC and GC-MS, using two columns of different polarities. Fifty-seven and 58 components were identified in each of the fruits, representing 99.2% and 99.5% of the isolates, respectively. The volatile profiles of both fruits were quite similar, both of which being dominated by alcohols (H. polyrhizus, 36.5%; H. undatus, 38.6%) and carboxylic acids (H. polyrhizus, 35.1%; H. undatus, 22.3%), with 1-hexanol and squalene as the two major components. The volatile constituents of H. polyrhizus showed stronger antibacterial activity than those of H. undatus when tested against five bacteria (Bacillus subtilis subsp. spizizenii, Escherichia coli, Klebsiella pneumonia, Pseudomonas stutzeri and Staphylococcus aureus) using the micro-dilution antibacterial assay. This is the first report for the volatile constituents and antibacterial acitivities of the both Hylocereus species. The phytochemical investigation on H. polyrhizus had led to the isolation and identification of six compounds. Myo-inositol (C1) was isolated from the methanolic fruit extract while octatriacont-1-ene (C2), lupeol (C3), stigmasterol (C4), a mixture of stigmasterol and β-sitosterol (C5) and quercetin (C6) were isolated from the chloroform extract of the stems. The structures of these compounds were elucidated by spectroscopic techniques such as IR, DP-MS, 1D-NMR, 2D-NMR and UV-Vis.